ANALISIS YURIDIS KESEPAKATAN MENENTUKAN HARGA ANTAR PENGUSAHA SEPEDA MOTOR (MATIC) PERSPEKTIF HUKUM PERDATA - Haris Yanis (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Based on the provisions regarding the legal requirements of an agreement as regulated in Article 1320 of the Civil Code, then in an agreement, the conditions for the validity of the agreement specified in the law of the article must be fulfilled. The conditions for the validity of the agreement as regulated in Article 1320 of the Civil Code are cumulative; it means that the non-fulfillment of one of the conditions of the provisions of the article will result in the cancellation or the agreement can be cancelled. This study aims to determine the legal provisions of the agreement in determining the price of an item among businessmen in the perspective of the Civil Code, and the validity along the legal consequences of an agreement or on agreements in determining the price of motorcycle among motorcycle entrepreneurs based on the Civil Code.From a civil law perspective, the alleged occurrence of a cartel carried out between PT. Yamaha Indonesia Motor Manufacturing (PT. YIMM) and PT. Astra Honda Motor (PT AHM) in selling automatic motorcycles type 110-125 cc has not fulfilled the elements of Article 5 of Law no. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. In this case, KPPU has not been able to fully prove the existence of an "agreement" between PT. Yamaha Indonesia Motor (PT. YIMM) and PT. Astra Honda Motor (PT AHM) in determining the price agreement. The legal consequence of price agreement in determining the prices based on a civil law perspective is an act that is against the law, namely Law no. 5 of 1999, so that an agreement or on agreements in determining the prices is an agreement or on agreements that is contrary to the law, which has legal consequences of the cancellation or get the cancellation of the agreement.  Keywords: Agreement, Motorcycle Entrepreneur, Civil Law.